2019
DOI: 10.1111/ejss.12843
|View full text |Cite
|
Sign up to set email alerts
|

Improving soil aggregation, aggregate‐associated C and N, and enzyme activities by green manure crops in the Loess Plateau of China

Abstract: Green manure and fertilization practices have substantial impacts on soil chemical and biological properties over time. A field experiment was conducted on Cumulic Haplustoll to investigate the effects of leguminous green manure (LGM) crops and nitrogen (N) fertilizer on dry‐stable soil aggregate distributions and stability, the concentrations of organic carbon (OC) and N in the bulk soil and separated aggregate fractions, and soil enzyme activities in dry croplands on the Loess Plateau of China. Species teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 33 publications
2
21
0
1
Order By: Relevance
“…Application of amendments including manure and crop straws have been proven to be effective agricultural practices when attempting to improve soil aggregation and crop yields 1 . Pig manure has improved macroaggregate percentage and aggregate associated C and N content 5 , 6 . Soybean green manure improved large aggregates (> 2 mm) greater than a control treatment 5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Application of amendments including manure and crop straws have been proven to be effective agricultural practices when attempting to improve soil aggregation and crop yields 1 . Pig manure has improved macroaggregate percentage and aggregate associated C and N content 5 , 6 . Soybean green manure improved large aggregates (> 2 mm) greater than a control treatment 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Pig manure has improved macroaggregate percentage and aggregate associated C and N content 5 , 6 . Soybean green manure improved large aggregates (> 2 mm) greater than a control treatment 5 . Also, rice straw incorporation alone or in compound with NPK fertilizers was generally effective in increasing water-stable aggregation 1 , and restricting release of small particles (< 10 µm) of an Inceptisols, due to an increase in soil organic carbon (SOC) 7 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that when organic matter such as animal manure, farm yard manure, or municipal wastes was applied to saline soils, sodium (Na + ) leaching can be accelerated through increasing soil porosity, hydraulic conductivity, and biopore networks, and reducing bulk density [15][16][17][18]. Furthermore, compost application can also decrease exchangeable sodium percentage (ESP) and increase water-holding capacity and aggregate stability [19,20]. In addition, organic matter application to saline soils may have positive effects on microbial biomass and enzymatic activities [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…In soil tectonics, infiltration is one of the main internal erosion processes, selectively eroding the fine particles that move through the voids formed by the coarser particles [14]. Green manure planting in high-latitude paddy fields can reduce soil consolidation caused by rainy seasons by increasing the content of water-stable aggregates and soil permeability [15], which is related to the soil colloid content caused by green manure root secretions and microbial enzyme activity [16]. Low-latitude rice fields are susceptible to water erosion caused by heavy rainfall during the winter season, and green manure varieties with a well-developed root system should be selected to protect the soil from nutrient loss in the topsoil.…”
Section: Physical and Chemical Propertiesmentioning
confidence: 99%